Performance Appraisal of a Stationary Diesel Engine with Different Pistons - and Dr. K. Vijaya Kumar Reddy2, K. Sri Rama Murthy1* (Recent Research in Science and Technology, 2010)
In this era of industrialization, due to rapid growth in energy sector, energy requirements for transportation and agricultural needs is ever increasing. At the same time due to depletion in fossil fuel sources, there is an urgent need to research for alternatives. Before the alternative sources are identified, there is a need towards improving the performance of existing engines. An attempt is made here to study the behaviour of a single cylinder, four stroke diesel engines with cast iron, cast iron coated with nickel chromium and aluminium pistons. The very aim of this experimentation is to find the suitability of different materials for piston towards better performance. Compared with the existing cast iron piston engine, brake thermal efficiency is increased by 9.12%, where brake specificÂ fuel consumption, exhaust gas temperature, mechanical efficiency andÂ volumetric efficiency are decreased by 8.3%, 2.05%, 5.24% and 0.75%Â respectively by using aluminium piston. Keywords: Diesel engine, Cast iron piston, Aluminium piston, Coated piston, Performance